Biomass supply chain optimisation via novel Biomass Element Life Cycle Analysis (BELCA). (1st January 2016) - Lim, Chun Hsion; Lam, Hon Loong
Highlights: Novel biomass supply chain optimisation via biomass element characteristic. Consider process waste as alternative resources in biomass supply chain network. Reuse potential biomass from process waste based on element characteristic analysis. Biomass Element Life Cycle Analysis approach improves existing supply chain system. Abstract: Negative environment impacts and security issues from fossil fuel based resource lead to the search of alternative sustainable resources, such as biomass. Biomass technology is limited by the complex biomass element characteristic and properties, and as well as high transportation cost. Unique property of biomass creates a gap in selection of biomass feedstock for each technology. Most of the technology developments are based on particular biomass species. This creates problems to implement the same technology in area without respective biomass, thus require more work to be done on specific biomass species available in that system. A novel technique – Biomass Element Life Cycle Analysis (BELCA) is introduced to tackle these problems. BELCA acts as a platform to study the element characteristic of each biomass from plantation site and biomass generated from process plant. This study allows better understanding of respective biomass characteristic for higher level of biomass utilisation and applications. The new approach integrates biomass resources with process feedstock via biomass element characteristic and optimised supply chain network for optimum biomass utilisation and application. Biomass characteristic is presented in a simple graphical approach to enhance the understanding and highlight their potential value. Combination of this method with biomass characteristic data bank will make the biomass selection easier. Biomass characteristic study enable integration of underutilised biomass into existing system, hence biomass industry can be improved. A biomass supply chain case study incorporated with BELCA approach is conducted. The result shows significant improvement of BELCA supply chain model over the existing system.